2011
DOI: 10.1002/ptr.3507
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Effects of Topical Formulations Containing a Combination of Ginkgo biloba and Green Tea Extracts

Abstract: The beneficial photoprotective effects of topical formulations containing combined extracts of Ginkgo biloba (GB) and green tea (GT) have not been investigated. The present study aims to assess the photoprotective effects of topical formulations containing GB and GT combined or not by applications on the dorsal skin of hairless mice prior to UVA/B irradiation. After 20 h, skin barrier damage (TEWL), erythema, histological alterations and sunburn cell formation were evaluated. The results showed that only extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…In an artificial skin culture model GTC decreased the level of MMPs production and increased TIMP-1 expression level, and reduced alterations in the extracellular matrix following application of UVA radiation [ 25 ]. A comparable UVA/UVB radiation study undertaken in a mouse model using EGCG and ginkgo biloba showed that the two extracts had a complimentary photoprotective effect, linked to a biological/free radical scavenging effect as opposed to a UV-filtering effect [ 7 ]. GTCs also play a role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In an artificial skin culture model GTC decreased the level of MMPs production and increased TIMP-1 expression level, and reduced alterations in the extracellular matrix following application of UVA radiation [ 25 ]. A comparable UVA/UVB radiation study undertaken in a mouse model using EGCG and ginkgo biloba showed that the two extracts had a complimentary photoprotective effect, linked to a biological/free radical scavenging effect as opposed to a UV-filtering effect [ 7 ]. GTCs also play a role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, most tests have been conducted by oral ingestion or topical application of these ingredients in inappropriate vehicles, which can alter the skin barrier. To be of practical use to dermatologists and to be safe and efficient, extracts must have physicochemical characteristics that permit their incorporation in adequate concentrations in a skin-compatible vehicle (e.g., gels, moisturizing creams) [34]. In this study, the capacity of the Morinda citrifolia extract, added to topical formulations (gels), to prevent or to treat UVA-UVB irradiation-induced skin damage in mice was evaluated.…”
Section: Discussionmentioning
confidence: 99%
“… 10 The Ginkgo fruits (nuts) are also known to have health benefits for prevention of cancer, cardiovascular, neurological disorder, and photoprotective effect. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%